LEISURE POSSIBILITIES: THE RELIGION AS ALTERNATIVE PRACTICAL (Fiep Bulletin - online, 2013)
The leisure, when understood in a multicultural perspective, does not have to neglect one of the aspects that the free time of Pentecostals fiduciary offices has organized, as religious leisure. If it has a fort I appeal to the adoption the practical ones leisure, as consequence of the development of the capitalism, the religious activity cannot be placed in a secondary space in this debate. It does not have as to disrespect the power of enchantment of the religious activities and its determinative paper as promotional of emotions and commotions, being acted as an entertainment of low cost, available, of free initiative and personal choice.
Keywords: Religion; Leisure; Free Time